2023
DOI: 10.3390/ani13132237
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Eimeria Inoculation Doses on Growth Performance, Daily Feed Intake, Gut Health, Gut Microbiota, Foot Pad Dermatitis, and Eimeria Gene Expression in Broilers Raised in Floor Pens for 35 Days

Janghan Choi,
Doyun Goo,
Milan Kumar Sharma
et al.

Abstract: The study was conducted to investigate the effects of different Eimeria inoculation doses on the growth performance, gut ecosystem, and body composition of broilers in floor pens for 35 days. A total of 750 15-day-old broilers were allocated to five experimental groups with six replicate pens. The five experimental groups included unchallenged control (CON); Eimeria dose 1 (ED1): E. acervulina: 31,250/E. maxima: 6250/E. tenella: 6250; Eimeria dose 2 (ED2): E. acervulina: 62,500/E. maxima: 12,500/E. tenella: 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 81 publications
(116 reference statements)
1
12
0
Order By: Relevance
“…The result of the current study indicates that Eimeria infection in hens at peak production negatively affects the laying hen performance (BW, BWG, FI, FCR, and HDEP). These results are in accordance with the previous studies by Choi et al (2023) , Teng et al (2020 , 2021 ), and Sharma et al (2022 a, b ). The linear reduction observed in BW and BWG in laying hens challenged with increasing doses of mixed Eimeria spp.…”
Section: Discussionsupporting
confidence: 94%
“…The result of the current study indicates that Eimeria infection in hens at peak production negatively affects the laying hen performance (BW, BWG, FI, FCR, and HDEP). These results are in accordance with the previous studies by Choi et al (2023) , Teng et al (2020 , 2021 ), and Sharma et al (2022 a, b ). The linear reduction observed in BW and BWG in laying hens challenged with increasing doses of mixed Eimeria spp.…”
Section: Discussionsupporting
confidence: 94%
“…Two time points were selected for performance recording and sample collection as multiple previous research showed that the infection peaks at 6-day postinoculation ( DPI ) and the birds start to recover at 9 DPI ( Teng et al, 2020 ; Choi et al, 2021 , 2023 ; Sharma et al, 2024 ). Body weight ( BW ) and feed intake ( FI ) were measured on d 14, 20, and 23 (0, 6, and 9 DPI) for calculating body weight gain ( BWG ) and feed conversion ratio ( FCR ).…”
Section: Methodsmentioning
confidence: 99%
“…In the current production practices, only Met is supplemented to meet the SAA requirements, producing no negative effects on the performance and health of the birds under normal and healthy conditions, as Cys can be produced through the metabolism of Met ( Bianchi et al, 2000 ; Albers, 2009 ; Bauchart-Thevret et al, 2009 ). However, under the conditions of Eimeria challenge, the normal functions of the intestines ( Teng et al, 2020 ; Choi et al, 2023 ) and liver ( Akhtar et al, 2012 ; Song et al, 2020 ; Blokker et al, 2022 ) can be compromised, potentially hindering the conversion of Met to Cys. This could lead to a deficient supply of Cys, which may further exacerbate the negative effects of coccidiosis on the growth and health of the birds.…”
Section: Introductionmentioning
confidence: 99%
“…One-way ANOVA and Tukey HSD tests were performed using JMP Pro 17 (SAS Institute, Cary, NC, USA) to compare the treatment groups. Statistical significance was set at a p -value < 0.05, and a p -value between 0.05 and 0.1 indicated a tendency toward significance [ 66 ]. Linear and quadratic regressions using LSMean contrast in JMP Pro 17 were used to assess the effects of increasing AFB1 doses on each parameter.…”
Section: Methodsmentioning
confidence: 99%